Risk Profile and Profitability on Mudharabah Financing at Bank Muamalat, Is There any Relation? - Dani, Rian; Mubyarto, Novi; Nengsih, Titin Agustin (Penerbit Goodwood, 2024)
Purpose: To find out whether there is an influence of the NPF and ROA variables on Mudharabah Financing at Bank Muamalat. If the NPF is greater, the Mudharabah Financing problems will increase and if the ROA is lower, the Mudharabah Financing will decrease further. Methodology/approach: Type of research used in this research was quantitative research. Source of Data used in this research was secondary data that obtained from quarterly financial reports published by Bank Muamalat for 2015-2022. Data analysis technique used in this research was Multiple Linear Regression Analysis. Results/findings: NPF partially has a significant negative effect on Mudharabah Financing with a sig value. Amounting to 0.024<0.05, the t-statistic value is -2.391. ROA partially has a significant positive effect on mudharabah financing with a sig value. Amounting to 0.002<0.05, and the t-statistic value is 3.355. NPF ROA together influences the dependent variable Mudharabah Financing with a sig value. 0.001<0.05. Limitations: This research is limited to Internal Bank variables such as NPF and ROA, which influence Mudharabah Financing. Other Internal and External Bank variables influence Mudharabah Financing. Contribution: Bank Muamalat Management must maintain the NPF ratio value of <2%, which has been determined by Bank Indonesia, so that the bank is in a healthy condition and can maintain the value of Mudharabah Financing. Bank Muamalat Management must raise more funds so that the bank has the opportunity to expand financing because ROA has a significant positive effect on Mudharabah Financing.